2001
DOI: 10.1177/147323000102900204
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes in Acute Exacerbations of Chronic Bronchitis: Comparison of Macrolides and Moxifloxacin from the Patient Perspective

Abstract: Moxifloxacin, a new respiratory quinolone, was compared with the macrolides azithromycin, clarithromycin and roxithromycin in a cohort study to assess clinical, safety and health-related outcomes of these antimicrobials in general practice settings. In total 332 patients with acute exacerbations of chronic bronchitis (AECB) each received one of the antimicrobial agents for a standard short course of therapy. Random allocation of therapeutic agents occurred by centre, not individuals, and the drugs were prescri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2003
2003
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 9 publications
1
14
0
2
Order By: Relevance
“…Levofloxacin and moxifloxacin are active against most of the strains of S. pneumoniae and H. influenzae and achieve high concentrations in bronchial secretions several times higher than the required MIC to treat these microorganisms [215][216][217][218][219]. In addition, they are active against Gram negative bacilli other than P. aeruginosa.…”
Section: Recommendationmentioning
confidence: 99%
“…Levofloxacin and moxifloxacin are active against most of the strains of S. pneumoniae and H. influenzae and achieve high concentrations in bronchial secretions several times higher than the required MIC to treat these microorganisms [215][216][217][218][219]. In addition, they are active against Gram negative bacilli other than P. aeruginosa.…”
Section: Recommendationmentioning
confidence: 99%
“…Four studies assessing pharmacological treatment and HRQL at two or more time points during an AECB and recovery period were identified [13,14,18,19]. In general, it appears that treatment is superior to no treatment, but there is little to recommend one treatment over another based on the instruments and duration of the studies identified here.…”
Section: Pharmacological Treatmentmentioning
confidence: 97%
“…Two studies were double-blind and randomized [13,14]; six others were randomized, but not blinded (often necessary because of the nature of intervention) [15][16][17][18][19][20]. One randomized study of pharmacological interventions was not randomized by patient, but rather by site [19].…”
Section: Study Design and Patient Populationmentioning
confidence: 99%
“…L'efficacia clinica e la tollerabilità della moxifloxacina nella CAP, nelle AECB e nelle ABS sono state studiate su un numero elevato di pazienti, nel corso di diversi trial multicentrici controllati, nazionali e internazionali, strutturati nella maggior parte come studi in doppio cieco [101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118].…”
Section: Efficacia Clinica E Batteriologica Nelle Infezioni Acute Delunclassified
“…L'efficacia e l'utilità cliniche della moxifloxacina nelle bronchiti croniche riacutizzate sono state confermate da alcuni studi condotti in aperto [112][113][114].…”
Section: Efficacia Della Moxifloxacina Nei Pazienti Con Polmonite Acqunclassified